PSD-95 protects the pancreas against pathological damage through p38 MAPK signaling pathway in acute pancreatitis. Issue 13 (July 2021) - Guo, Yinan; Hu, Weikai; Wang, Xueyan; Li, Chunyun; Cui, Tianyu; Liu, Ruixia; He, Junqi; Yin, Chenghong
Acute pancreatitis is one of the leading causes of gastrointestinal disorder-related hospitalizations, yet its pathogenesis remains to be fully elucidated. Postsynaptic density protein-95 (PSD-95) is closely associated with tissue inflammation and injury. We aimed to investigate the expression of PSD-95 in pancreatic acinar cells, and its function in regulating the inflammatory response and pancreatic pathological damage in acute pancreatitis. A mouse model of edematous acute pancreatitis was induced with caerulein and lipopolysaccharide in C57BL/6 mice. Tat-N-dimer was injected to inhibit the PSD-95 activity separately, or simultaneously with SB203580, inhibitor of p38 MAPK phosphorylation. Rat pancreatic acinar cells AR42J were cultured with 1 μM caerulein to build a cell model of acute pancreatitis. PSD-95-knockdown and negative control cell lines were constructed by lentiviral transfection of AR42J cells. Paraffin-embedded pancreatic tissue samples were processed for routine HE staining to evaluate the pathological changes of human and mouse pancreatic tissues. Serum amylase and inflammatory cytokine levels were detected with specific ELISA kits. Immunofluorescence, immunohistochemical, Western-blot, and qRT-PCR were used to detect the expression levels of PSD-95, p38, and phosphorylated p38. Our findings showed that PSD-95 is expressed in the pancreatic tissues of humans, C57BL/6 mice, and AR42J cells, primarily in the cytoplasm. PSD-95 expression increased at 2 h, reaching the peak at 6 h in mice and 12 h in AR42J cells. IL-6, IL-8, and TNF-α increased within 2 h of disease induction. The pancreatic histopathologic score was greater in the PSD-95 inhibition group compared with the control ( P  < 0.05), while it was lesser when phosphorylation of p38 MAPK was inhibited compared with the PSD-95 inhibition group ( P  < 0.05). Moreover, phosphorylation of p38 MAPK increased statistically after PSD-95 knocked-down. In conclusion, PSD-95 effectively influences the pathological damage of the pancreas in acute pancreatitis by affecting the phosphorylation of p38 MAPK.